2021
DOI: 10.3390/ijerph18168294
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Deviant Peer Affiliation in the Relation between Cyber-Victimization, Tobacco and Alcohol Use, and Age Differences

Abstract: Cyber-victimization, tobacco and alcohol use are all prominent public health problems among adolescents throughout the world. Against this background, this study examined the association between cyber-victimization and tobacco and alcohol use, as well as the moderating role of deviant peer affiliation and the potential age differences among elementary, middle, and high school students. A survey conducted among 1488 school students (aged 9–19 years, consisting of 702 elementary school students, 318 middle schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
(56 reference statements)
2
6
0
Order By: Relevance
“…Tests of the second half of the mediation process (i.e., deviant peer affiliation → NSSI) found that deviant peer affiliation was positively associated with adolescent NSSI, consistent with prior research (Wei et al, 2021). One potential explanation is that deviant peer affiliation may lead to adolescents' problem behaviors, such as drinking (Sun et al, 2021), so these adolescents may experience more rejection and isolation by typical peers (Jiang et al, 2015). This in turn could lead to adolescents' negative emotions such as depression (Platt et al, 2013).…”
Section: The Mediating Role Of Deviant Peer Affiliationsupporting
confidence: 77%
See 1 more Smart Citation
“…Tests of the second half of the mediation process (i.e., deviant peer affiliation → NSSI) found that deviant peer affiliation was positively associated with adolescent NSSI, consistent with prior research (Wei et al, 2021). One potential explanation is that deviant peer affiliation may lead to adolescents' problem behaviors, such as drinking (Sun et al, 2021), so these adolescents may experience more rejection and isolation by typical peers (Jiang et al, 2015). This in turn could lead to adolescents' negative emotions such as depression (Platt et al, 2013).…”
Section: The Mediating Role Of Deviant Peer Affiliationsupporting
confidence: 77%
“…Previous studies have confirmed that deviant peer affiliation is an important risk factor for Chinese adolescents' aggressive behavior (Lin et al, 2020), tobacco and alcohol use (Sun et al, 2021), and internet gaming addiction (Tian et al, 2019). Moreover, several studies have shown that behaviors such as drinking, internet addiction, and aggressive behavior were positively correlated with NSSI among Chinese adolescents (Zhang et al, 2019;Pang and Wang, 2020;Gui et al, 2021).…”
Section: Deviant Peer Affiliation As a Potential Mediatormentioning
confidence: 90%
“…Considering the average score, the higher the score, the more undesirable the peer behavior. The questionnaire has been shown to be reliable and valid [ 55 , 56 ]. In this study, Cronbach’s α was 0.78.…”
Section: Methodsmentioning
confidence: 99%
“…It may cause great harm to adolescents’ health and adaptation—tobacco and alcohol use cause brain damage [ 2 ], poor academic performance [ 3 , 4 ], and aggressive behaviors [ 5 ] among adolescents. Therefore, its influencing factors have been the focus of researchers, among which peer relationship, especially deviant peer affiliation, has received attention [ 6 , 7 , 8 , 9 ]. This is because the influence of peer relationships surpasses other interpersonal relationships (such as parent–child relationships) and becomes one of the main factors affecting adolescents’ psychological and behavioral development [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, adolescents are interacting more with their peers, who have a greater impact on them than their parents [ 10 ]. Different peer factors and relationships may have different effects on adolescents, among which deviant peer affiliation may have a negative effect [ 6 ]. Deviant adolescents exhibit a high-incidence group of problem behaviors (such as smoking, drinking, skipping classes, etc.)…”
Section: Introductionmentioning
confidence: 99%